Investigation of structural and magnetic properties of Heusler Fe2+xMn1−xAl alloys by first principles method. Issue 5 (15th April 2014) - Buchelnikov, V. D.; Zagrebin, M. A.; Sokolovskiy, V. V.; Taranenko, I. A.; Zayak, A. T.
Abstract: Heusler alloys Fe2+x Mn1−x Al exhibit intricate interplay between structural parameters and a number of competing magnetic states. In this work, we use first principles calculations to investigate crystal lattice relaxation of these alloys and their coupling to the magnetic order, with a particular focus on the tetragonal distortions characterised by the c/a ratio. We find that the calculated equilibrium cubic phase is antiferromagnetic, while a metastable ferrimagnetic state is also present, being higher in energy only by an order of kT, suggesting a close competition of these two magnetic states in real materials. The ferrimagnetic state corresponds better to the experimental data. The tetragonal distortions and the changes of volume alter dramatically the balance in magnetic coupling by favouring the ferromagnetic state. In order to understand this magneto‐structural coupling, we obtained ( a, c/a ) diagrams that show regions of relative stability of the ferromagnetic and antiferromagnetic states Our calculations suggest an opportunity for tuning magnetic properties of Fe2+x Mn1−x Al alloys with strain and composition. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)